Emergency Presentations With Nonspecific Complaints—the Burden of Morbidity and the Spectrum of Underlying Disease: Nonspecific Complaints and Underlying Disease - Karakoumis, Julia (Medicine (Baltimore), 2015)
The prevalence of diagnoses, morbidity, and mortality of patients with nonspecific complaints (NSC) presenting to the emergency department (ED) is unknown. To determine the prevalence of diagnoses, acute morbidity, and mortality of patients with NSC. Prospective observational study with a 30-day follow-up. Patients presenting to 2 EDs were enrolled by a study team and diagnosed according to the World Health Organization ICD-10 System. Of 217,699 presentations to the ED from May 2007 through to February 2011, a total of 1300 patients were enrolled. After exclusion of 90 patients who fulfilled exclusion criteria, 1210 patients were analyzed. No patient was lost to follow-up. In patients with NSC, the underlying diseases were spread throughout 18 chapters of the ICD-10. A total of 58.7% of the patients were diagnosed with acute morbidity. Thirty-day mortality was 6.4% overall. Patients with acute morbidity and suffering from heart failure and pneumonia had mortalities >15%; patients lacking acute morbidity, but suffering from functional impairment or depression/anxiety had mortalities of 0%. Although the history did not allow any prediction, age and sex were predictive of morbidity and mortality. The differential diagnoses in patients presenting with NSC is broad. Acute morbidity and mortality were high in the presented cohort, the predictors of morbidity and mortality being age and sex rather than the nature of the complaints. Urgently needed management strategies could be based on these results. ClinicalTrials.gov (#NCT00920491).